Histological Studies on the Duodenum of the Guinea Pig (Cavia porcellus) in Postnatal Age Groups - K. Raja, (Indian Journal of Veterinary Anatomy, 2022)
In the present study, the wall of the duodenum of guinea pigs was composed of four layers namely tunicamucosa, tunica submucosa, tunica muscularis and tunica serosa in all the age groups i.e 0-2 weeks to 16-32weeks–old guinea pigs (n=24). Villi were taller and had a finger like appearance except in 0-2 weeks-old guineapigs. Surface epithelium was lined by the simple columnar epithelium with few goblet cells, along with this fewglobular leukocytes and intra epithelial cells were also observed in all the age groups. Enterochromaffin cellswere few observed stain at the basal part of the crypts and less in the surface epithelium. Lamina propria wascomposed of loose connective tissue. Crypts of Lieberkuhn present throughout the lamina propria. Tunicasubmucosa comprised of loose connective tissue mainly of collagen and reticular fibres and few elastic fibres inthe wall of the blood vessels. Submucosa of the duodenum showed the Brunner's glands of various sizes. Innercircular and outer longitudinal muscle layers were observed in the tunica muscularis. The mean height and widthof the villi, height of the columnar cells and thickness of the tunica muscularis increased as the age advanced in allthe age groups.